Repeat Users of Chat Reference: An Exploratory Study. Issue 3 (2nd October 2021) - Hurley, David A.
ABSTRACT: Libraries have long used patrons' willingness to return as a metric for assessing reference services, but have not measured actual return rates for this service. Knowing if our user base is a small number of highly engaged patrons, or many patrons who visit only once, has implications for service improvements, marketing, and assessment. This study establishes 28% as the baseline return rate for chat reference at one research university, with 62% of all sessions coming from repeat users. Predictors of whether a patron would return after their first session are affiliation (e.g., whether they are faculty, graduate student, undergraduate, staff, or not affiliated with the university), the duration of the session, and where on the library website the chat was initiated. The librarian assisting, wait time, and the patron's own rating of the chat are among the factors that are not predictive. Further research into why patrons do or do not return, and what constitutes a good return rate, is recommended.